Gross job flows in transition countries: Results from company accounts data for Bulgaria, Estonia and Romania - Giulia Faggio; Jozef Konings (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 1998)
This paper studies patterns of gross job creation and destruction in Bulgaria, Estonia and Romania. To this end a unique data set of more than 1600 Bulgarian, 350 Estonian and 3700 Romanian firms in various sectors and located in various regions is used. We find that gross job destruction dominates job creation, but the latter is picking up as transition progresses. We also find that small firms have higher gross job flows than larger ones. There are important sectoral, industry and regional differences in gross job reallocation. In addition, there is a lot of heterogeneity within sectors and within regions, as most of the excess job reallocation can be explained by employment shift within the same sector or region. There are also important differences across countries. Estonia is characterised by higher job flows rates than Bulgaria and Romania. This indicates that there is more firm restructuring going on in Estonia than in the other two countries. Bulgaria and Romania exhibit instead a similar sectoral pattern at the two-digit sectoral level, which can be explained by technological differences across sectors that hold independent of the country. However, if only the manufacturing sector is considered, the more traditional sector, institutional differences play an important role in explaining job flows variations in Bulgaria and Romania. Furthermore, the interaction between the two effects can better account for variations in the real churning of jobs.
Keywords: J6; P2; 330; job creation; job destruction; transition economies